2019
DOI: 10.1007/s11606-019-04934-7
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Long-Term Oral Bisphosphonate Use

Abstract: This study was conducted within Kaiser Permanente Northern California (KPNC) and approved by the KPNC Institutional Review Board. Conflict of Interest: The following conflicts of interest are reported: Joan Lo has received research funding from Amgen, Inc., and Sanofi Aventis and Malini Chandra has received research funding from Amgen, not pertaining to this study; Bruce Ettinger has served as an expert witness pertaining to litigation involving teriparatide (Teva Pharmaceuticals). The remaining authors have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Our findings suggest that among long-term BP users, several expected factors appear to influence treatment continuation, specifically low BMD, recent fracture, and era of treatment initiation. Our data indicate an interesting secular trend in BP continuation, also reported elsewhere 21 -since 2008, BP use beyond the initial 5 years of treatment was less common than in the previous years.…”
Section: ■■ Conclusionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings suggest that among long-term BP users, several expected factors appear to influence treatment continuation, specifically low BMD, recent fracture, and era of treatment initiation. Our data indicate an interesting secular trend in BP continuation, also reported elsewhere 21 -since 2008, BP use beyond the initial 5 years of treatment was less common than in the previous years.…”
Section: ■■ Conclusionsupporting
confidence: 86%
“…The current study confirms our previous finding reported from a northern California cohort of women receiving long-term BP therapy, where a decline in continuation of longterm therapy (up to 3 and 5 years) was also evident in later compared with earlier treatment eras. 21…”
Section: ■■ Discussionmentioning
confidence: 99%